Peningkatan Keterampilan Deteksi Dini Hipertensi Berbasis Pemberdayaan Karang Taruna di Bedahan, Sawangan, Depok - Nur Sholihah; Wulan Septiana; Celsa Indri Putri; Regita Dewiarti; Muhammmad Imam Fadhillah; Promisetyaningrum Fitri Nurani; Een Kurnaesih (Progran Studi Farmasi Universitas Mandala Waluya, 2026)
Hypertension is a common health issue that is often undetected until it leads to serious complications. In Bedahan Village, Depok City, hypertension is a significant health concern, with the number of affected individuals aged 15 years and older reaching 6,048 in 2023. This study focuses on enhancing early detection skills for hypertension among the youth members of Karang Taruna using a participatory and practical approach. The methods employed include education and hands-on training in the use of digital sphygmomanometers. The results indicate a significant improvement in participants' abilities to operate the sphygmomanometer and accurately interpret the readings, which has the potential to reduce the prevalence of hypertension. These findings underscore the importance of involving youth communities, such as Karang Taruna, as public health agents in the early detection of hypertension. This strategy can be applied to address various other health issues within the community.